The emerging role and clinical implication of human exonic circular RNA. Issue 8 (3rd August 2017) - Lyu, Dongbin; Huang, Shenglin
ABSTRACT: Circular RNA from backspliced exons (or exonic circular RNA, circRNA) is a type of covalently closed non-colinear RNA that was recently rediscovered in eukaryotes. Although circRNAs are often expressed at low levels, emerging evidence indicates that many circRNAs are linked to physiological development and various diseases. Notably, circRNAs have been shown to serve as oncogenic stimuli or tumor suppressors in cancer. circRNAs may regulate gene expression through different mechanisms. In addition, circRNAs have been shown to be useful as biomarkers of diseases due to their stability, specific expression and relation to diseases both in cells and in extracellular fluid. This review summarizes current knowledge of human circRNAs and discusses the emerging role and clinical implication of these multifarious transcripts.